Hungary : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2013)
Non-performing loans (NPLs) were found to respond to macroeconomic conditions, such as GDP growth, unemployment, and inflation; there are also strong feedback effects from the banking system to the real economy. This suggests that the high NPLs that many CESEE countries currently face adversely affect the pace of economic recovery. The note also evaluates different policy options to achieve permanent fiscal consolidation in Hungary. A fiscal consolidation based on a reduction in government transfers can stimulate labor participation, and a resulting increase in the returns to capital can increase investment and output in the long term.